2010
DOI: 10.1007/s11148-010-9244-2
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical studies of pyrophyllite of the Nikol’sk deposit

Abstract: Elemental chemical analysis shows that pyrophyllite of the Nikol'sk deposit does not contain iron oxide. Due to the high content in pyrophyllite ore of pyrophyllite and diaspore (corresponding 80 and 4%) the amount of aluminum oxide within exceeds 30%, that will facilitate preparation of high quality acid-resistant materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The results of reflected light microscopy showed that the impurities are present in rare amounts and occur as very fine-grained, anhedral crystals disseminated in the rock following the foliation. Moreover, these impurities are evident in pyrite and hematite forms, which exist in pyrophyllite as oxide and sulfide minerals (Abdrakhimova ,2010;Bozkaya et al, 2007;Wiewióra et al ,1993).The results also indicated that detected disseminated pyrite is noted altered to hematite in the rim and within pyrite. Figure 3 shows high pyrite reflectance, white-gray color, and dissolved at the rim and within it to hematite (brown color).…”
Section: Microscopic Studies Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of reflected light microscopy showed that the impurities are present in rare amounts and occur as very fine-grained, anhedral crystals disseminated in the rock following the foliation. Moreover, these impurities are evident in pyrite and hematite forms, which exist in pyrophyllite as oxide and sulfide minerals (Abdrakhimova ,2010;Bozkaya et al, 2007;Wiewióra et al ,1993).The results also indicated that detected disseminated pyrite is noted altered to hematite in the rim and within pyrite. Figure 3 shows high pyrite reflectance, white-gray color, and dissolved at the rim and within it to hematite (brown color).…”
Section: Microscopic Studies Resultsmentioning
confidence: 79%
“…Pyrophyllite is a phyllosilicate mineral comprised mainly of aluminum silicate hydroxide [Al 2 Si 4 O 10 (OH) 2 ] and is commonly found with other minerals such as talc and kaolinite, rutile, epidote, quartz, and mica (Abdrakhimova, 2010;Ali et al ,2021;Jeong et al, 2017;Kogel et al,2006)that will facilitate preparation of high quality acid-resistant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have used electrolysis, flotation, and electrification to remove sulfur, chlorine, iron, and titanium from non-metallic minerals [20,28,33]. For pyrophyllite, gravity separation techniques, flotation, magnetic separation, and leaching by ammonia and oxalic acid have been explored [1,8,18,28,34,35]. Furthermore, microwaves combined with sequential magnetic separation treatment have been used and considered as a promising method for upgrading low-grade pyrophyllite ore [19,36].…”
Section: Gradementioning
confidence: 99%
“…Pyrophyllite is a hydrous aluminum silicate with the chemical formula Al 2 Si 4 O 10 (OH) 2 and is commonly associated with other minerals such as quartz, mica, kaolinite, epidote, and rutile [1][2][3]. The pure pyrophyllite is composed of 28.3% Al 2 O 3 , 66.7% SiO 2 , and 5% H 2 O on weight bases [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation